Studi Kapasitas Way Dan Kinerja Simpang Pada Jalan Z.A Pagar Alam â Universitas Lampung - Pramuka - Citra, Jimmy; Purba, Alexander; Hadi, Martono (Jurnal Rekayasa Sipil dan Desain, 2018)
This research focuses on a number of intersection performances along Z.A Pagar Alam Street. The problems that sometimes occurs when some vehicles should be stoped repeatedly on the intersection approach. Data collection is done by direct survey on the three intersections. The data collected consist of volume and intersection geometric. The degree of saturation on each approach in intersection I (Pramuka) is 0.68 (East), 0.68 (West), 0.65 (North). The total delays on intersection I (Pramuka) is 63217.28 pcu.second. The degree of saturation on each approach of intersection II (MBK) is 0,75 (East), 0,72 (West), 0,74 (South). Total delays on intersection II (MBK) is 67544,59 pcu.second. The degree of saturation on each approach in intersection III (Unila) is 0,72 (East), 0,69 (South), 0,67 (West). Total delays on intersection III (Unila) is 50404,36 pcu.second. After the operation of flyover on the two intersections then the total delay changed. The total delay at intersection I dropped to 9370,44 pcu.second. The total delay at intersection II has decreased to 7885,08 pcu.second.Keywords : Degree of saturation, total delay, intersection.